TINJAUAN YURIDIS PENISTAAN MAKAM ULAMA DI INDONESIA - Masruroh, Ainul; Afiyah, Siti; Wibowo, Ari (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2023)
The act of verbally insulting a deceased person is a crime regulated by the legal rules in force in Indonesia (KUHP). Open access allows various lectures and writings to become narratives that encourage hostility and hatred. In this case, insulting the cleric's grave gave rise to polarization and demonstrations. For this reason, it is necessary to study in more depth the elements of criminal liability that can be given to perpetrators of insults. The aim of this research is to find out how positive law regulates acts of insulting people who have died, even though the person being insulted has died. The research carried out is normative juridical research using primary, secondary, and tertiary legal materials. After the data is collected, it is then analyzed systematically and linked to legal materials. The results of this research show that even though the object of insult is a person who has died, the law regulates criminal acts of insult, which can be applied to insulting the graves of ulama. These regulations are regulated in articles 320 and 321 of the Criminal Code and articles 27 and 28 of the ITE Law.